TINJAUAN TERHADAP PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DALAM MENDAPATKAN JAMINAN DI RUMAH SAKIT TINGKAT IV DI KOTA SAMARINDA - Chelsea, Lasameil (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
AbstractThe Health Social Security Organizing Agency is a non-profit body formed by the Government to administer health social security that is directly responsible to the President to provide health insurance to all communities in order to obtain a more decent life.The  author  in  conducting  this  study  uses  an  empirical  juridical  method,  namely  research  carried  out  by  collecting  data  directly  from  competent  parties  in  connection  with  the  object  under  study,  for  this  reason  an  interview  method  is  conducted  with  employees  and  agencies  related  to  the  object  of  this  research  to  obtain  primary  data.This  study  aims  to  determine  the  criteria  for  health  insurance  provided  by  Health Social Security Organizing Agency as  well as  the  health  services  provided  by  Hospital  Level  IV  Samarinda  that  serving  general  patients  and  participating  patiens  Health Social Security Organizing Agency.